Mobile learning acceptance framework among Malaysian formal part-time learners / Noor Maizatulshima Muhammad Sabri - Noor Maizatulshima , Muhammad Sabri (2021)
The performance of adult learners has become a significant challenge in education due to the difficulties in their ability to manage their time while maintaining focus. This also contributes to the problem of balancing the demands imposed through learning and other personal life pressures and obligations. This particular group of learners, including formal part-time learners, are mostly adults who need to manage multiple commitments, including family matters, social life, careers, health, finance in addition to learning. In the digital world, every aspect of education involves some form of technology. Mobile technology has quickly evolved to become a ‘pocket device’ in providing 24/7 learning practices without the restrictions of time nor place. Thus, mobile learning (m-Learning) constitutes any form of learning activities through mobile devices with convenient learning experiences. However, limited empirical studies have investigated the behaviour of adult learners that represent the characteristics associated with formal part-time learners in measuring the acceptance level of this technology. Therefore, this study aims to analyse the role of andragogy theory using adult learner principles in determining m-Learning technology acceptance among formal part-time learners. The categorisation of formal part-time learners was undertaken using specific attributes via Structural Model Measurement (SMM) that enabled the researcher to discover the unique predictive values of self-directed learning, prior experience, learning readiness, and the orientation to learn in the context of formal part-time learners’ acceptance, in addition to the assimilation of the Unified Theory of Acceptance and Use of Technology (UTAUT) variables. The hypotheses were developed, followed by developing a survey questionnaire that was distributed to and completed by 394 formal part-time learners in Malaysia. The reflective SMM was then analysed using SmartPLS (v 3.2.7), where the results indicated that the reliability and validity were satisfactorily achieved. All six attributes fulfilled the threshold, whereas the hypothesis regarding the variables of prior experience and orientation to learning was not accepted. Accordingly, a guideline was developed and recommended to enhance formal part-time learner’s intention to accept m-Learning based on the proposed framework. It is anticipated that the findings of this study will add to the body of knowledge in this field by providing further insights and understanding on the possibility of formal part-time learners’ attributes that influence their acceptance of m-Learning in promoting a better learning environment. The results also offer further direction in determining the success rate of formal part-time learners with respect to the distance learning process. Finally, it is anticipated that the proposed framework will address all the requirements needed by the adult learners.